Regulation and regulatory risk in the face of large transmission investment - Gert Brunekreeft; Roland Meyer (Jacobs University Bremen, Bremer Energie Institut, 2011)
Most transmission systems in Europe are currently in need of large network expansions, in particular to cope with increasing shares of load remote renewable energy sources. Given that the scope for further cost reductions is largely exhausted, we observe a paradigm shift into the direction of implementing more cost-pass-through elements into price-based regulation to strengthen the necessary investment incentives. Regulatory emphasis is shifting from costreductions to promoting investment. Obstacles to investments arise in particular from regulatory risk and efficiency risk. Addressing these topics, we recommend a move towards more cost-based approaches, with ex-ante investment approval and less reliance on ex-post benchmarking.
Keywords: 330; regulation; regulatory risk; network investments